2014
DOI: 10.1016/j.virol.2013.11.041
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic activity of APOBEC3F is required for efficient restriction of Vif-deficient human immunodeficiency virus

Abstract: APOBEC3 proteins are DNA cytosine deaminases that restrict the replication of human immunodeficiency virus deficient in the counterdefense protein Vif. Here, we address the capacity of APOBEC3F to restrict via deaminase-dependent and -independent mechanisms by monitoring spreading infections in diverse T cell lines. Our data indicate that only a deaminase-proficient protein is capable of long-term restriction of Vif-deficient HIV in T cells, analogous to prior reports for APOBEC3G. This indicates that the prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…Since H9 cells express similar levels of A3F and A3DE than A3.01 cells (Dang et al, 2006; Rose et al, 2005), we infer that they also do not significantly contribute to the non-permissive phenotype in H9 cells. This conclusion is consistent with our previous observation that stably expressed A3F has overall negligible antiviral activity when compared to A3G (Miyagi et al, 2010) although there is no unified opinion on that in the literature (Albin et al, 2014; Bishop et al, 2004; Chaipan et al, 2013; Holmes et al, 2007; Liddament et al, 2004; Mulder et al, 2010). (ii) Increasing A3G expression in A3.01 cells to levels comparable to H9 or CD4+ T cells using wild type A3G effectively blocked replication of Vif-null HIV-1 suggesting that a relatively modest increase in A3G expression is sufficient to completely restrict Vif-null virus (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Since H9 cells express similar levels of A3F and A3DE than A3.01 cells (Dang et al, 2006; Rose et al, 2005), we infer that they also do not significantly contribute to the non-permissive phenotype in H9 cells. This conclusion is consistent with our previous observation that stably expressed A3F has overall negligible antiviral activity when compared to A3G (Miyagi et al, 2010) although there is no unified opinion on that in the literature (Albin et al, 2014; Bishop et al, 2004; Chaipan et al, 2013; Holmes et al, 2007; Liddament et al, 2004; Mulder et al, 2010). (ii) Increasing A3G expression in A3.01 cells to levels comparable to H9 or CD4+ T cells using wild type A3G effectively blocked replication of Vif-null HIV-1 suggesting that a relatively modest increase in A3G expression is sufficient to completely restrict Vif-null virus (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…The virus replicated slowly, and viral loads at 6 weeks were reduced by 80% relative to those of the wild type, NLCSFV3. While these findings strongly suggest a significant impact on HIV-1 replication by A3F, the interpretation of the result is not straightforward because the tetra-alanine mutation may impact other Vif activities in addition to A3F degradation (58).…”
Section: Discussionmentioning
confidence: 90%
“…The biggest surprise is that a high-resolution structure was obtained without zinc in the active site. All previous data of APOBEC crystal and NMR structures [9, 10, 12–22, 34, 35], as well as structures of phylogenetically related enzymes (CD, CDD1, ADAR, ADAT [36–51]), indicate zinc coordination at the active site.. For all tested enzymes, mutagenesis studies have shown that the conserved zinc coordinating residues are essential for catalytic activity ( e.g ., A3F H249, E251, C280, and C283 [4–6]). However, the active site glutamic acid may be dispensable for zinc binding because changing this residue in A3A (E72A) or in the distantly related Blasticidin S. deaminase (E56Q) did not prevent the protein from coordinating zinc as evidenced by crystal structures [9, 52].…”
Section: Discussionmentioning
confidence: 99%
“…Mutagenesis studies have demonstrated that conserved amino acids in the zinc-coordinating motif are essential for catalysis (reviews cited above). For instance, mutating the catalytic glutamate or the zinc-coordinating residues (three cysteines or, in some enzymes, two cysteines and one histidine) completely abolishes catalytic activity and, in most instances, also abrogates HIV-1 restriction activity ( e.g ., studies on A3F [4–6]).…”
Section: Introductionmentioning
confidence: 99%